If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + -1b = r Reorder the terms: -1b + 5p = r Solving -1b + 5p = r Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-5p' to each side of the equation. -1b + 5p + -5p = -5p + r Combine like terms: 5p + -5p = 0 -1b + 0 = -5p + r -1b = -5p + r Divide each side by '-1'. b = 5p + -1r Simplifying b = 5p + -1r
| -2x^3-2x^2+12x=0 | | 6a-1=2+2a | | 2x^2+3x=54 | | n-17.9=31.05 | | 6[5+2(3-8)-3]= | | -3x=150 | | 10(9-y)= | | -x^2+x+42=0 | | 2a-5=3a | | 6(11x+2)= | | 4w-9=-15 | | 5x^2+8x+k=0 | | 22-2(x-4)=8-5(x+1) | | 7p-2=54+3p | | 5(-4w-8)= | | 3.2(y+1)=2(1.4y-3) | | 2t^2+5t-10=0 | | 97-2x=16x+23 | | 10-2x=-6 | | 5x+2-2x= | | 2z-31=-9z | | -19x-34=54-x | | 5.85b=8.68+3.86b | | 4(d-8)= | | 177-5x=5x+12 | | 3(-3k+5)= | | (x*13.5)+(.5x*5)=1400 | | (x*13.5)+(y*5)=1400 | | 6(-y-4)= | | .33(b-9)=b+9 | | 3.2=0.4n | | 2(y+4)=8 |